Optimization and validation of algorithm of histologic investigation of cone biopsy of cervix uteri. - Lukyanchuk, O. V.; Rosha, L. G. (Морфологія / Morphologia / Morfologìâ, 2014)
Backgrund. Adequate treatment of patients with cervical cancer remains an urgent problem of modern cancer care. In the study protocol of College of American Pathologists the algorithm of summary formation in cases of invasive cervical cancer is described in details, but there is no algorithm for the material collection. Objective. The purpose of the study was to optimize and improve the quality of histologic investigation of cervix uteri preparations. Methods. An algorithm for the pathomorphological investigation of conus bioptates of cervix uteri was created. It was introduced into the work of pathologic anatomy department of the Center of Reconstructive and Reparative Medicine (Univercity Clinic) of Odessa National Medical University. 40 macropreparations of conus bioptates of cervix uteri with cervical intraepithelial neoplasia of 2nd and 3rd stage and microinvasive carcinoma were studied. Results. Unified investigation of cone biopsy of cervix uteri guarantees precise diagnostics of neoplasia of cervix uteri, and also controls the quality of conization of cervix uteri. Investigation of consultation material from other departments of pathologic anatomy proves that introduction of such algorithms is not a material for discussion, but a necessity. Conclusion. Modern pathologic anatomy service requires the implementation of the protocols for investigation of cone biopsy of cervix uteri. The introduced protocol corresponds to all the requirements of oncomorphology, involves all stages of the investigation, and can be recommended for use in the work of pathologic anatomy departments.